2008
DOI: 10.4141/cjps07056
|View full text |Cite
|
Sign up to set email alerts
|

Light interception and radiation use efficiency of fern- and unifoliate-leaf chickpea cultivars

Abstract: , T. 2008. Light interception and radiation use efficiency of fern-and unifoliateleaf chickpea cultivars. Can. J. Plant Sci. 88: 1025Á1034. A chickpea (Cicer arietinum L.) crop with rapid leaf development, high solar radiation interception, and efficient use of radiation can maximize the yield potential in a short-season typical of the Northern Great Plains. This study determined the effects of cultivars varying in leaf architecture on light interception (LI) and radiation use efficiency (RUE) in chickpea. Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Interestingly, there was a wide genotypic diversity in fAPAR i in all points measured covering from vegetative to flowering stages, and at flowering, it varied up to 25% across the genotypes assessed (Table 3). These results might differ with environment since we only measured 1 year, but similar genotypic variation also has been observed for light interception in lentils and chickpeas (Hanlan et al, 2006;Li et al, 2008). There were also differences across pulses, in a study comparing chickpea, lentil, narrow-leafed lupin and field pea found that narrow-leafed lupin intercepted more radiation than the other pulse species (Ayaz et al, 2004).…”
Section: Genotypic Diversity In Light Interceptionmentioning
confidence: 71%
See 1 more Smart Citation
“…Interestingly, there was a wide genotypic diversity in fAPAR i in all points measured covering from vegetative to flowering stages, and at flowering, it varied up to 25% across the genotypes assessed (Table 3). These results might differ with environment since we only measured 1 year, but similar genotypic variation also has been observed for light interception in lentils and chickpeas (Hanlan et al, 2006;Li et al, 2008). There were also differences across pulses, in a study comparing chickpea, lentil, narrow-leafed lupin and field pea found that narrow-leafed lupin intercepted more radiation than the other pulse species (Ayaz et al, 2004).…”
Section: Genotypic Diversity In Light Interceptionmentioning
confidence: 71%
“…Variation in lentil canopy architecture has been moderately associated with genotypic variation in light interception ( McKenzie and Hill, 1991 ; Hanlan et al, 2006 ). Plant height in wheat and leaf type in chickpeas have also been associated with changes in LI or RUE ( Miralles and Slafer, 1997 ; Li et al, 2008 ). Studies in lentils have shown variation in architectural traits such as branch angle, number of branches and plant height ( Erskine and Goodrich, 1991 ; Hanlan et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the longer growing period, these genotypes attained higher PH with greater IL, NPP, and BPP. However, late flowering genotypes, as identified in NL and LL treatments ( Table 2 ), performed better due to maximum light-harvesting, radiation use efficiency, and higher energy production ( Li et al., 2008 ; Bai et al., 2016 ; Shafiq et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies under semiarid growing conditions showed that blight severity was lower on cultivars with pinnate leaves (such as Amit) than cultivars with unifoliate leaf type (such as CDC Xena) (Gan et al, 2003a). The cultivars with pinnate leaves have greater total leaf area and improved radiation interception than cultivars with unifoliate leaves (Li et al, 2008). This difference in plant morphology may influence retention efficiency of fungicides applied as sprays to the top of the plant canopy (Byer et al, 2006; Armstrong‐Cho et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The reaction of commercial cultivars currently available in the northern Great Plains ranges from partially resistant to highly susceptible, but no cultivar is totally resistant (Chandirasekaran et al, 2009). Cultivars with pinnate leaves generally have higher levels of resistance than those with unifoliate leaves (Gan et al, 2003a), partly due to differences in canopy architecture associated with leaf types (Li et al, 2008). However, resistance typically declines after flowering regardless of leaf type (Chongo and Gossen, 2001).…”
mentioning
confidence: 99%